(untitled) (Medico Legal Update, 2021)
In this study, extraction of the banana peels were done by two solvent kinds and water. Cytotoxic activity of the extracts were tested by using assay of MTT. Inhibition of cells was 68.2% when banana peel was extracted by hexane, and the effect of its cytotoxicity was the highest at 100 ?g/ml. On the other hand, growth inhibition of MCF-7 cells was recorded at this concentration. While, ethanol extract was at the second stage according to its cytotoxicity which reached 54.1% followed by watery extract which showed 46.9%.Antimicrobial activity of banana peel extractswas tested against some pathogenic bacteria and showed the capacity to have abroad range of inhibition activities against isolates E. coli, klebsiellaspp, S. aureus, P. aeruginosa, extracts demonstrated inhibition zones which were greater than 20,10,15 mm against E. coli,klebsiella andstaph. spp. respectively, but did not affect P. aeroginosa Also, experimental animals were exposured to these extracts. It was revealed that NTEC (CNF2) toxin made few chronic inflammatory cells proliferation, hyperplasia of lymphoid tissue and some cases of atrophy in the villi. Current results showed low impact on tissue cells when banana peel extracts were used.